2021
DOI: 10.4103/jfmpc.jfmpc_2449_20
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic and psychosocial correlates of substance abuse among street children

Abstract: Context: India is now witnessing steady increase of substance abuse in younger age group. Street life is a major reason in addition to curiosity, unawareness of harm, migration, peer pressure. Aims: To assess the prevalence, pattern and related factors of substance use and stress among the street living children. Settings and Design: This street-based observational, cross sectional survey included 150 street children living in vicinity of rai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 14 publications
3
6
0
Order By: Relevance
“…Our results also point to the debilitating effects on physical health (Ayaya & Esamai, 2001;Sah et al, 2019) and the indifference and neglect that street children more generally also experience (Ali & de Muynck, 2005). The potential protective influence of educational institutions mirrors that found by Islam et al (2014) and Basu et al (2021). In contrast to Merriman and Guerin (2007) who found the aspiration of becoming a teacher and a doctor to be the most commonly held in their sample of Calcutta street children, we found children express different ones not necessarily associated with a higher socio-economic status (SES) or high education requirements.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Our results also point to the debilitating effects on physical health (Ayaya & Esamai, 2001;Sah et al, 2019) and the indifference and neglect that street children more generally also experience (Ali & de Muynck, 2005). The potential protective influence of educational institutions mirrors that found by Islam et al (2014) and Basu et al (2021). In contrast to Merriman and Guerin (2007) who found the aspiration of becoming a teacher and a doctor to be the most commonly held in their sample of Calcutta street children, we found children express different ones not necessarily associated with a higher socio-economic status (SES) or high education requirements.…”
Section: Discussionsupporting
confidence: 72%
“…While we recognize that these categories are not very neat and clean ones, and the term itself has been argued to be problematic (Panter-Brick, 2002), evidence points to street-involved adolescents being far more vulnerable to inhalant abuse and its health consequences than those not involved with the street (Nath et al, 2016). Although the definitions and methods do not remain constant, estimated prevalence rates of inhalant abuse among street-involved children and adolescents (with and without other substances) vary from 88.46% in Butwal, Nepal (Sah et al, 2019), 70.71% in Guwahati, India (Islam et al, 2014), 41.3% in Kolkata, India (Basu et al, 2021), and 67% in Eldoret, Kenya (Embleton et al, 2013). Drawing from a systematic review of the literature on the health status of street children and youth, Woan et al (2013, p. 318) observe that "there is an inhalant use epidemic in low and middleincome countries."…”
Section: Inhalant Abuse and Its Prevalence Among Street-involved Adol...mentioning
confidence: 99%
“…They also reported a 32.2 per cent history of drug and alcohol consumption and 72.2 per cent of smoking. A cross-sectional study of 156 street adolescents in India showed that most adolescents had primary education, and the prevalence of substance abuse was high (Basu et al, 2021). Experiencing poverty, forced labour and the lack of a healthy family environment and proper control in this population leads to dropping out of school at an early age and social harm (Oppong Asante et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Industrial glues and petrol were found to be used in high proportions, followed by tobacco, alcohol, and cannabis. [20][21][22][23][24][25] The substances they use are frequently selected for their low price, widespread availability, and ability to induce a sense of euphoria instantly. 1 Poverty, urbanization, breakdown of families, domestic violence, and child labor were important correlates of substance abuse in street children.…”
Section: Data From Street Childrenmentioning
confidence: 99%